SEJARAH INTELEKTUAL ISLAM: KONTRIBUSI DAN PENGARUH PEMIKIRAN Al-GHAZALI TERHADAP DUNIA ISLAM ABAD KE 11 M - Saidin Hamzah; Abdullah; Usman; Kurais (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
This research discusses al-Ghazali's contribution and thoughts to the Islamic world in the 11th century M. The focus of the study includes al-Ghazali's success in integrating the teachings of Sufism into the mainstream of Islamic thought, reforming Islamic education, and providing criticism of philosophy that enriches Islamic theological discourse. The aim of this research is to explore the contribution and influence of al-Ghazali's thought on the development of the Islamic world, in three main aspects, namely, Islamic spirituality, the Islamic education curriculum, and the development of Islamic philosophy. Researchers use historical research methods which consist of four stages, namely, heuristics, criticism, interpretation, and historiography with a literature review approach by collecting data in the form of books, journals, documents, as well as sources of data and information relevant to the study. This research found that al-Ghazali's main contributions, such as reforms in Islamic theology, criticism of philosophy, and his influence on education and religious thought. In addition, al-Ghazali's intellectual legacy not only enriches Islamic traditions but also offers relevant perspectives in facing contemporary challenges, making his work an important reference in modern Islamic studies today.